PENGARUH PERSEPSI KETIDAKADILAN IMBALAN DAN KEPUASAN IMBALAN TERHADAP INTENSI KELUAR KARYAWAN DALUMAN VILLA SEMINYAK - Hasbi, Muhamad; Piartrini, Putu Saroyeni (E-Jurnal Manajemen, 2016)
The study objectives are perception of reward imbalance having positive affect on intention to quit and reward satisfaction having negative affect on intention quit. Samples was 39 respondent’s, all of Daluman Villa employee’s, selecting by using cencus method with multiple regression analyst as the data analysis technique. Data’s of this research collected from 39 employee’s of Daluman Villa by filling a questioner’s. Result of analyst reported that 1) Perception of reward imbalance have a positive affect on intention to quit; 2) Reward satisfaction have a negative affect on intention to quit of Daluman Villa employee’s. Implication of this study was suggested to still effort to hold the employee’s from quiting, villa management had make employee’s trust was having treated so fairly considered Indonesian Ordinance’s and work aggrement’s, then having feel satisfaction in rewarding as appreciation of the employee’s performance and after that all employee’s wouldn’t having an intention to quit.
Keywords: perception of reward imbalance, reward satisfaction, intention to quit